IMPLEMENTASI PENDEKATAN PEMBELAJARAN STEAM BERBASIS MODEL PJBL UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SDN 14 BENGKAYANG - Yulita Ling Ling; Hendrikus Torimtubun (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the implementation of a STEAM learning approach based on the Project-Based Learning (PjBL) model to enhance student interest and learning outcomes in IPAS subjects for Class V at SDN 14 Bengkayang. The research subjects involved 25 fifth-grade students from Class 5A during the 2023/2024 school year. The research method employed was classroom action research (PTK), utilizing data collection techniques such as observation, questionnaires, and tests. The study was conducted over two cycles, each consisting of three meetings. The findings indicate that the implementation of the STEAM learning approach, grounded in the PjBL model, significantly improved student interest and learning outcomes in the IPAS subject. This suggests that integrating STEAM and PjBL can effectively engage students and enhance their academic performance in science and social studies.